2016
DOI: 10.5539/ass.v12n2p93
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Engineering Students’ Responses to Flipped Classroom Methodology in the United Arab Emirates

Abstract: The aim of this study was to analyse student responses to the introduction of flipped learning methodology at an institution of higher education in the northern region of the United Arab Emirates to identify potential relationships between and among the responses and to determine underlying factors guiding the responses. A survey questionnaire was developed by a team of faculty and sent to students via online survey software. The analysis employed dimension reduction techniques to ascertain underlying factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…From the questionnaire distributed to teachers, it was revealed that the advantages of the flipped classroom are the need of more time for material preparation and technological problems faced by some students who are not familiar with the platform used. Adapted from (Gough et al, 2017;Khodr & Waller, 2016) The teachers also confirmed the questionnaire distribution findings related to flipped classrooms' drawbacks during the in-depth interview. It was stated that material preparation in a flipped classroom setting is time-consuming.…”
Section: Teachers' Viewsupporting
confidence: 67%
See 3 more Smart Citations
“…From the questionnaire distributed to teachers, it was revealed that the advantages of the flipped classroom are the need of more time for material preparation and technological problems faced by some students who are not familiar with the platform used. Adapted from (Gough et al, 2017;Khodr & Waller, 2016) The teachers also confirmed the questionnaire distribution findings related to flipped classrooms' drawbacks during the in-depth interview. It was stated that material preparation in a flipped classroom setting is time-consuming.…”
Section: Teachers' Viewsupporting
confidence: 67%
“…Table 2 summarizes the mean and standard deviation from different survey questions related to teachers' responses to the strengths of flipped classroom methodology with CALL in the EFL setting. (Gough et al, 2017;Khodr & Waller, 2016) Further, the results of an in-depth interview with teachers also revealed some facts. One of them is that the flipped classroom provides flexibility to teachers in implementing it.…”
Section: Teachers' Viewmentioning
confidence: 87%
See 2 more Smart Citations
“…The questionnaire was adapted from Khodr and Waller (2016) and Gough et al (2017) and customized to be suitable for research questions and related theories. It consisted of 20 question items.…”
Section: Methodsmentioning
confidence: 99%